Whether cross-border e-commerce exports promote regional economic growth? Evidence from China - Ping, Guo; Hamzah, Hanny Zurina; Lee, Chin (Johar Education Society, Pakistan, 2024)
The current study aims to discover the impact of cross-border e-commerce (CBEC) exports on regional economic growth in China. A benchmark regression via the fixed panel effect model was conducted (using STATA software) based on Chinese provincial data from 2015 to 2020. The results demonstrated that CBEC exports significantly increased regional economic growth in China. The heterogeneity test also revealed CBEC exports have a significant positive impact in less developed regions rather than in more developed regions. Furthermore, the threshold effect test discovered that the technological input of manufacturing enterprises produced a non-linear significant impact on CBEC exports to elevate economic growth. When the proportion of technological input to GDP is less than the threshold of 0.031, the significant impact of CBEC exports on economic growth was larger; and then the impact became smaller and insignificant after the threshold. The findings suggested the Chinese government should vigorously develop CBEC export in terms of improvements in trade facilitation, CBEC talent training, and encouraging enterprises to explore different oversea markets. Simultaneously, attention should be paid to providing more policy support for the development of CBEC exports in less developed areas, and emphasis should be placed on guiding manufacturing enterprises to make rational use of research and development (R&D) funds.